Analysis of Bone Histomorphometry in Rat and Guinea Pig Animal Models Subject to Hypoxia - Usategui-Martín, Ricardo; Del Real, Álvaro; Sainz-Aja, José A.; Prieto-Lloret, Jesús; Olea, Elena; Rocher, Asunción; Rigual, Ricardo J.; Riancho, José A.; Pérez-Castrillón, José Luis (International journal of molecular sciences, 2022)
Hypoxia may be associated with alterations in bone remodeling, but the published results are contradictory. The aim of this study was to characterize the bone morphometry changes subject to hypoxia for a better understanding of the bone response to hypoxia and its possible clinical consequences on the bone metabolism. This study analyzed the bone morphometry parameters by micro-computed tomography (μCT) in rat and guinea pig normobaric hypoxia models. Adult male and female Wistar rats were exposed to chronic hypoxia for 7 and 15 days. Additionally, adult male guinea pigs were exposed to chronic hypoxia for 15 days. The results showed that rats exposed to chronic constant and intermittent hypoxic conditions had a worse trabecular and cortical bone health than control rats (under a normoxic condition). Rats under chronic constant hypoxia were associated with a more deteriorated cortical tibia thickness, trabecular femur and tibia bone volume over the total volume (BV/TV), tibia trabecular number (Tb.N), and trabecular femur and tibia bone mineral density (BMD). In the case of chronic intermittent hypoxia, rats subjected to intermittent hypoxia had a lower cortical femur tissue mineral density (TMD), lower trabecular tibia BV/TV, and lower trabecular thickness (Tb.Th) of the tibia and lower tibia Tb.N. The results also showed that obese rats under a hypoxic condition had worse values for the femur and tibia BV/TV, tibia trabecular separation (Tb.Sp), femur and tibia Tb.N, and BMD for the femur and tibia than normoweight rats under a hypoxic condition. In conclusion, hypoxia and obesity may modify bone remodeling, and thus bone microarchitecture, and they might lead to reductions in the bone strength and therefore increase the risk of fragility fracture.